Conceptualization of Optimistic Models for the World in Paremic Picture of the World - Semenenko, Nataliya N.; Mashukova, Darya A.; Smelkovskaja, Marina J.; Lazutkina, Olesia A. (Journal of History Culture and Art Research, 2017)
The description of language expression of an ethno cultural stereotype in assessment of optimistic approach to judgment of a role of trials destiny provides in human life is offered. The optimistic outlook model is considered as integrative linguo-cognitive area which valuable dominants are directly connected with points, key for national sphere of concepts. The algorithm of a descriptive technique is presented on the example of cognitive and pragmatical modeling of semantics in the Russian proverbs of theme groups "Destiny - Patience - Hope" and "Patience - Hope" from the collection "Proverbs of the Russian People" of V. I. Dahl. The area of paremic verbalization of cognitive category "Optimism" is considered taking into account polyconceptuality of national aphorisms maintenance and ambivalence of the ethno culture major stereotypes assessment concluded in them. Linguo-cognitive potential of paremias in representation of optimistic outlook model is defined with aphoristic value of paremias, pragmatical recommendation expressed in them and a valuable semantic core.